The strategic concept for the Lithuanian bioeconomy: insights for niche bioenergy sectors [version 1; peer review: 2 approved, 1 approved with reservations] - Akvilė Aleksandravičienė; Vlada Vitunskienė; Agnė Dapkuvienė; Jonas Čaplikas (Open Research Europe, 2023)
This article describes a strategic concept for the Lithuanian bioeconomy that was developed as a deliverable of the Task 1.5 in the BIOEAST’sUP H2020 project. We aimed to create a conceptual basis for the preparation of a national bioeconomy strategy and/or action plan in order to initiate a deeper discussion about the strategically oriented development of a knowledge-based circular bioeconomy in Lithuania. Our strategic insights are focused on two niche energy sectors like biofuels and biogas. The results of the SWOT analysis reveal that, in Lithuania, a synthesis of the biofuels and biogas sectors' strategic directions is necessary to develop over-arching national bioeconomy-appropriate strategic actions, such as market intervention actions, research, innovation and education actions, as well as governance and policy actions.